The solve of tactical and fire tasks during overcoming obstacle course - Penkov V. І.; Sutiushev Т. А.; Shkorbatov, Yu. H.; Magda І. Yu.; Buchatskyi, D. V.; Hulia, V. V. (Honor and Law, 2019)
The results of field research possibility by personnel solve tactical and fire tasks during overcoming the obstacle, as well as forms and methods of training cadets in the field are considered.